PROGRAM BIMBINGAN DAN KONSELING UNTUK MENGEMBANGKAN EMPATI PESERTA DIDIK REGULER TERHADAP PESERTA DIDIK BERKEBUTUHAN KHUSUS KELAS X DI SEKOLAH MENENGAH ATAS - Lani Cahyani; Herdi Herdi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This research aims to develop a guidance and counseling program to improve the empathy ability of regular students towards students with special needs grade X at SMA CIS Depok. This study is based on the findings of the assessment results using the IRI (Interpersonal Reactivity Index) instrument which shows that the empathy level of regular students is still low so that it often disturbs ABK students, The method used in this study is reaseach and development.  The final result of this research is in the form of producing a product for the development of guidance and counseling programs to improve students' empathy skills.